Characterization of Begomoviruses Sampled during Severe Epidemics in Tomato Cultivars Carrying the Ty-1 Gene - Torre, Covadonga; Donaire, Livia; Gómez-Aix, Cristina; Juárez, Miguel; Peterschmitt, Michel; Urbino, Cica; Hernando, Yolanda; Agüero, Jesús; Aranda, Miguel A. (International journal of molecular sciences, 2018)
Tomato yellow leaf curl virus (TYLCV, genus Begomovirus, family Geminiviridae) is a major species that causes a tomato disease for which resistant tomato hybrids (mainly carriers of the Ty-1/Ty-3 gene) are being used widely. We have characterized begomoviruses severely affecting resistant tomato crops in Southeast Spain. Circular DNA was prepared from samples by rolling circle amplification, and sequenced by massive sequencing (2015) or cloning and Sanger sequencing (2016). Thus, 23 complete sequences were determined, all belonging to the TYLCV Israel strain (TYLCV-IL). Massive sequencing also revealed the absence of other geminiviral and beta-satellite sequences. A phylogenetic analysis showed that the Spanish isolates belonged to two groups, one related to early TYLCV-IL isolates in the area (Group 1), and another (Group 2) closely related to El Jadida (Morocco) isolates, suggesting a recent introduction. The most parsimonious evolutionary scenario suggested that the TYLCV isolates of Group 2 are back recombinant isolates derived from TYLCV-IS76, a recombinant virus currently predominating in Moroccan epidemics. Thus, an infectious Group 2 clone (TYLCV-Mu15) was constructed and used in in planta competition assays against TYLCV-IS76. TYLCV-Mu15 predominated in single infections, whereas TYLCV-IS76 did so in mixed infections, providing credibility to a scenario of co-occurrence of both types of isolates.